2020
DOI: 10.1088/1361-6463/ab7351
|View full text |Cite
|
Sign up to set email alerts
|

Reduced plume oscillation amplitude in hollow cathode discharge due to enhanced electron emission from keeper electrode

Abstract: Inspired by the fact that ionization oscillations in hollow cathode plume are triggered by electron loss on keeper electrode, this paper replaced the material of keeper orifice plate with emissive ones in order to re-compensate the electron loss and checked the influence on plume oscillations. Results show that plume oscillations were indeed sensitive to exterior electron emission. When keeper orifice plate was LaB6 and short-circuited with cathode negative electrode instead of electrically floating, the oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…From tantalum (Ta) to LaB 6 to BaO, the work function became lower and emission from the keeper orifice plate became higher. As can be seen, plume oscillations were not always suppressed with more keeper emission [13]. It was estimated that the lowest amplitude (∼40% lower) came when thermal emission and secondary electron emission together were almost equal to the electron beam loss on the keeper boundaries.…”
Section: Impact Of Keeper Materialsmentioning
confidence: 98%
See 3 more Smart Citations
“…From tantalum (Ta) to LaB 6 to BaO, the work function became lower and emission from the keeper orifice plate became higher. As can be seen, plume oscillations were not always suppressed with more keeper emission [13]. It was estimated that the lowest amplitude (∼40% lower) came when thermal emission and secondary electron emission together were almost equal to the electron beam loss on the keeper boundaries.…”
Section: Impact Of Keeper Materialsmentioning
confidence: 98%
“…The trigger point happened to coincide with the point where electron relative amplitude was equal to ion relative amplitude, indicating that the triggering process also involves electron-ion non-equilibrium. In fact, the ion energy distribution function (IEDF) in the cathode plume did indeed shift to higher/lower energies with the keeper material changes [13], and therefore with the upstream/downstream movement of the step region. Currently the physics in the plume is more about electronion non-equilibrium, which is generally expected in lowtemperature plasmas.…”
Section: Trigger Point Of Step Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oscillations were coherent with the potential fluctuations of the keeper. In their subsequent work [11] the authors replaced the material of the keeper orifice plate with the emissive material to compensate for the electron loss. The results obtained showed that the amplitude of oscillations dropped by 60%.…”
Section: Introductionmentioning
confidence: 99%